Comparative genomic analysis of isoproturon‐mineralizing sphingomonads reveals the isoproturon catabolic mechanism. (15th July 2016) - Yan, Xin; Gu, Tao; Yi, Zhongquan; Huang, Junwei; Liu, Xiaowei; Zhang, Ji; Xu, Xihui; Xin, Zhihong; Hong, Qing; He, Jian; Spain, Jim C.; Li, Shunpeng; et al.
Summary: The worldwide use of the phenylurea herbicide, isoproturon (IPU), has resulted in considerable concern about its environmental fate. Although many microbial metabolites of IPU are known and IPU‐mineralizing bacteria have been isolated, the molecular mechanism of IPU catabolism has not been elucidated yet. In this study, complete genes that encode the conserved IPU catabolic pathway were revealed, based on comparative analysis of the genomes of three IPU‐mineralizing sphingomonads and subsequent experimental validation. The complete genes included a novel hydrolase gene ddhA, which is responsible for the cleavage of the urea side chain of the IPU demethylated products; a distinct aniline dioxygenase gene cluster adoQTA1A2BR, which has a broad substrate range; and an inducible catechol meta ‐cleavage pathway gene cluster adoXEGKLIJC . Furthermore, the initial mono‐ N ‐demethylation genes pdmAB were further confirmed to be involved in the successive N ‐demethylation of the IPU mono‐ N ‐demethylated product. These IPU‐catabolic genes were organized into four transcription units and distributed on three plasmids. They were flanked by multiple mobile genetic elements and highly conserved among IPU‐mineralizing sphingomonads. The elucidation of the molecular mechanism of IPU catabolism will enhance our understanding of the microbial mineralization of IPU and provide insights into the evolutionary scenario of the conserved IPU‐catabolic pathway.